Tracer Study Alumni: Upaya Peningkatan Layanan Pembelajaran Program Studi Pendidikan Agama Islam UHAMKA - Lismawati Lismawati; Shobah Shofariyani Iryanti (Universitas Muhammadiyah Prof Dr Hamka, 2020)
The research objectives of the PAI UHAMKA tracer study are to analyze the personal data of graduates, the views of graduates regarding the education services provided, the level of user satisfaction related to the professional competence of graduates, and the implementation of Al Islam and Muhammadiyah values ​​for graduates in the workplace and society. This research is a quantitative descriptive research through a survey approach which includes four stages: 1) developing concepts and instruments; 2) data collection 3) data analysis and 4) reporting. The research samples were graduates of PAI UHAMKA in 2016. For the data analysis stage, a mix method was used with the Sequential Explanatory model. The results showed 79% of PAI UHAMKA graduates in 2016 already had jobs with the majority working in companies / agencies / government institutions and companies / agencies / private institutions. The level of competence mastered by PAI UHAMKA graduates in 2016 is that knowledge in the field or discipline occupies the highest result. AIK coaching has an impact on the worship obedience of graduates, namely 48% answered fairly and 52% answered high.